AUTHENTIC ASSESSMENT IN EFL CLASSROOMS: SENIOR HIGH SCHOOL TEACHERS’ PROBLEMS - Winny Berliana; Friscilla Wulan Tersta (Lingua Scientia, 2024)
This study aimed to research the current problems faced by English teachers in senior high schools in Indonesia in applying authentic assessment for reading skills. In the 21st century, learning language focuses on creating students’ skills and critical literacy, communication, collaboration, and creativity to survive in this world. To achieve those aspects, Emancipated Curriculum (Kurikulum Merdeka) provides an authentic assessment that reflects learners’ real competencies, such as attitudes, knowledge, and skills. Emancipated Curriculum class emphasizes that teachers use authentic assessment to assess the process and results of teaching and learning activities. Furthermore, this study is a qualitative method with a case study approach. This study concerned three (3) English teachers who have used authentic assessment in the classroom. In collecting data, the researcher used documentation, observation, and interviews. In this study, the observation data is in the form of the implementation Emancipated Curriculum in the teaching and learning process by English teachers in class. The researcher made observations regarding the implementation of the Emancipated Curriculum such as the way teachers teach, student activities, and methods used by teachers in the teaching and learning process. Interviews were also used as data for this study. The researcher wrote down the results of the interview in English in the form of words from the explanation results. From the results of data analysis can be concluded that all English teachers in those schools already implemented authentic assessments. They faced several problems in implementing authentic assessment for reading skills, such as students’ lack of vocabulary, teachers’ lack of knowledge about authentic assessment, and limited time allocation. This study is hoped to give beneficial information related to the implementation of authentic assessment for reading skills.